Investigation of scattered dose in a mouse phantom model for pre-clinical dosimetry studies. (December 2021) - Entezam, Amir; Fielding, Andrew; Moi, Davide; Bradley, David; Ratnayake, Gishan; Sim, Lucy; Kralik, Chelsea; Fontanarosa, Davide
Abstract: Tissue-equivalent phantoms are suitable tools for radiation dosimetry investigations. The goal of this study was to determine the scattered dose in a simple phantom model of a mouse with a xenographic tumour using experimental dose measurements and Monte-Carlo calculations. We manufactured a cubic polymethyl methacrylate (PMMA) phantom with an extrusion on its side to model both normal tissue and xenograft tumour of a tumour-bearing mouse. The phantom was positioned in a novel add-on collimator, designed by our research group, to enable targeted irradiation of the xenograft tumour with a dose of 20 Gy using a 137 Cs gamma irradiator. EBT3 GAFchromic film was utilized to measure the dose distribution within the phantom. EGSnrc MC code was used to simulate the irradiation system and to calculate the dose distribution in the phantom for comparison with the film dose measurements. Good agreement was observed between film dose measurements and simulation results based on gamma index analysis. The results demonstrate that the out of field dose (dose to the normal tissue) is of the order 8–9% of the prescribed dose when irradiating the xenographic tumour of the phantom. Our physical phantom is a useful tool to assess the out of field dose when irradiating xenographic tumours. Highlights: A mouse phantom with a xenographic tumour was manufactured for dosimetry. Out of field dose was determined when irradiating the xenographic tumour model. Monte Carlo modelling of the phantom irradiation was created for dose calculation. Gamma analysis was used to compare the measured and calculated dose profiles.